Pro-immigrant legislation and financial inclusion: The effects of sanctuary policies on the mortgage market - David Zuchowski (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Does pro-immigrant legislation improve financial inclusion? This paper examines how granting safe havens for immigrants impacts Hispanics' financial behavior and discrimination against them in the U.S. mortgage market. To identify the effect, I take advantage of the staggered implementation of sanctuary policies across counties between 2010 and 2021. Using an event study approach, I find that sanctuary policies increase the demand for mortgages among Hispanics. I also find evidence of a decrease in the rejection rates of mortgage loans requested by Hispanics in counties that implemented sanctuary policies. Politically volatile and Republican-leaning states are the main drivers of the reduction in this potential discriminatory behavior. Taken together, the findings underscore the importance of inclusive public policies in promoting financial inclusion of immigrants. – – Fördern immigrantenfreundliche Gesetze die finanzielle Inklusion? Diese Studie untersucht, wie die Gewährung von sicheren Zufluchtsorten für Immigranten das Finanzverhalten von Hispanics und die Diskriminierung gegen sie auf dem US-amerikanischen Hypothekenmarkt beeinflusst. Um den Effekt zu identifizieren, mache ich Gebrauch von der zeitlich gestaffelten Einführung sogenannter Sanctuary Policies in den Kreisen in den USA zwischen 2010 und 2021. Mit Hilfe eines Ereignisstudienansatzes komme ich zu dem Ergebnis, dass Sanctuary Policies die Nachfrage nach Hypotheken unter Hispanics erhöhen. Es gibt auch Hinweise auf eine Verringerung der Ablehnungsquoten von Hypothekenanträgen von Hispanics in Kreisen, die Sanctuary Policies umgesetzt haben. Kreise in politisch instabilen und republikanisch geprägten Bundesstaaten sind die Haupttreiber der Reduzierung dieses potenziell diskriminierenden Verhaltens. Insgesamt unterstreichen die Ergebnisse die Bedeutung von inklusiven Gesetzen zur Förderung der finanziellen Integration von Einwanderern.
Keywords: G21; J15; J68; K37; R21; 330; Sanctuary policies; immigration policy; mortgages; financial inclusion